Temperature-resistant composite modified material for well cementation cement and preparation method of temperature-resistant composite modified material
By using temperature-resistant composite modified materials for cement cement in high-temperature and ultra-high temperature environments of deep wells/ultra-deep wells, the problem of cement stone strength decline is solved, and the high-temperature compressive strength and toughness is improved, which meets the cementing needs of deep wells/ultra-deep wells, and has the advantages of green and environmental protection and cost-effectiveness.
Patent Information
- Application Number
- CN202411876626.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The prior art is difficult to effectively cement the well in the high temperature and ultra-high temperature environment of deep wells/ultra-deep wells, resulting in the decline of cement stone strength and the inability to seal the wellbore for a long time.
A temperature-resistant composite modified material for cementing cement is used, which includes strength modifier type I, strength modifier type II and toughness modifier. Through the synergistic action of these components, the crystal form, calcium-silicon ratio and pore structure of cement stone are regulated, and its high-temperature compressive strength and toughness are improved.
Effectively prevent the strength of cement stone from declining, improve its high-temperature compressive strength and toughness, meet the high-temperature cementing needs of deep wells/ultra-deep wells, and also has the characteristics of green and environmental protection, low cost and excellent performance.
Smart Images

Figure BDA0005197048850000081 
Figure BDA0005197048850000091 
Figure BDA0005197048850000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cementing materials for oil and gas field development, and in particular to a temperature-resistant composite modified material for cementing cement and a preparation method thereof. Background Art
[0002] As oil and gas exploration and development continue to go deeper, the exploration of deep resources has become an important direction for further exploration in the current oil industry. The deep ground field is a new field that will be a major strategic successor to China's future oil and gas exploration and development. The high-temperature downhole environment in deep and ultra-deep wells may cause the strength of cement stone to decrease, making it difficult to ensure that the oil and gas wells can effectively isolate the wellbore annulus for a long time after a successful cementing. The commonly used method at present is to add about 30-40% quartz sand to alleviate the decline in strength. However, the addition of quartz sand will significantly increase the elastic modulus of cement stone. Moreover, as the temperature increases, the sand-added cement system will still experience a decline in strength. Therefore, it is of great significance to develop a new high-temperature resistant and tough cement system.
[0003] Application No. 201910669046.5 discloses an ultra-high temperature elastic toughening agent for oil well cementing and its composition. The ultra-high temperature elastic toughening agent includes the following components blended by weight: 60% to 90% polytetrafluoroethylene rubber powder, 5% to 20% basalt fiber, and 5% to 20% nano alumina fiber.
[0004] Application No. 201910040381.9 discloses a high temperature resistant toughness material and its preparation method. The invention provides a high temperature resistant toughness material for cementing slurry, which includes the following components by weight: 10-20 parts of latex powder; 10-40 parts of modified rubber powder; 20-50 parts of polyimide resin; 5-10 parts of aminosilane coupling agent; 15-60 parts of modified nanotubes; the nanotubes in the modified nanotubes are carbon nanotubes and / or boron nitride nanotubes.
[0005] Application No. 201910694360.9 discloses a cementitious composition, a composite cementitious material and a cementing fluid. The cementitious composition comprises a silicon-aluminum admixture, a calcium-silicon admixture, a reinforcing material and a toughening material. The composite cementitious material comprises cement and the above-mentioned cementitious composition.
[0006] Application No. 201610937961.4 discloses a high-temperature oil well cement stone elastic material and a preparation method. The elastic material is prepared from raw materials including the following components: 100 parts by weight of hydrogenated styrene-butadiene block copolymer powder; 20-30 parts by weight of silica fume; 0-10 parts by weight of alkylphenol ether ammonium sulfate. The preparation method comprises: adding the raw materials according to the amount to the PCS particle composite system to obtain the high-temperature oil well cement stone elastic material.
[0007] Although the above-mentioned prior art has made breakthroughs in the compressive strength and toughness of cement paste, it can no longer meet the high temperature and ultra-high temperature cementing requirements faced by deep wells / ultra-deep wells. The present invention provides a temperature-resistant composite modified material for oil and gas well cementing cement, which can effectively prevent the strength decline of cement paste and improve the toughness of cement paste. Summary of the invention
[0008] In order to overcome the defects and shortcomings in the above-mentioned prior art, the present invention provides a heat-resistant composite modified material for cementing cement and a preparation method thereof. The heat-resistant composite modified material for cementing cement can effectively prevent the strength decline of cement stone and improve the toughness of cement stone.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] In one aspect, a heat-resistant composite modified material for cementing is provided, comprising the following raw materials by weight percentage:
[0011] Strength modifier type I: 30-40wt%;
[0012] Strength modifier type II: 55-60wt%;
[0013] Toughness modifier: 5-10wt%.
[0014] Furthermore, the strength modifier type I is a mixture of waste glass powder, tungsten tailings powder and fused quartz sand in a mass ratio of (1-2):(1-2):1.
[0015] Furthermore, the SiO2 content of the waste glass powder is ≥75wt%, and the powder particle size is 800 mesh; the SiO2 content of the tungsten tailings powder is ≥70wt%, the Al2O3 content is ≥10wt%, and the powder particle size is 325 mesh; the SiO2 content of the fused quartz sand is ≥99wt%, and the powder particle size is 325 mesh.
[0016] Furthermore, the strength modifier type II is prepared by mixing strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2, and the preparation method is as follows:
[0017] S11, mixing the strength stabilizing material A and the crystal inducing material and placing them in a sealed stirring tank, using anhydrous ethanol as a solvent with a liquid-to-solid ratio of 5:1, stirring at room temperature for 48 hours to form slurry A;
[0018] S12, performing solid-liquid separation and drying on slurry A to obtain powder A;
[0019] S13, mix the powder A and the strength stabilizing material B evenly to obtain a strength modifier type II.
[0020] Furthermore, the strength stabilizing material A is formed by mixing waste siliceous shale, biomass slag and coal gasification slag in a mass ratio of 2:1:1;
[0021] Preferably, the SiO2 content of the waste siliceous shale is ≥85wt%, and the waste siliceous shale is crushed and ground to form a powder with a particle size of 600 mesh;
[0022] Preferably, the SiO2 content of the biomass slag is ≥65wt%, the Al2O3 content is ≥15wt%, and the biomass slag is dried and ground to form a powder with a particle size of 600 mesh;
[0023] Preferably, the coal gasification slag has a SiO2 content of ≥55wt%, an Al2O3 content of ≥20wt%, a carbon content of ≥10wt%, and a particle size of 375 mesh;
[0024] The strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder and forsterite powder in a mass ratio of 1:1:2;
[0025] Preferably, the SiO2 content of the nanoclay is ≥47wt%, and the Al2O3 content is ≥40wt%;
[0026] Preferably, the MgO content of the waste magnesia brick powder is ≥90wt%, and the powder particle size is 325 mesh;
[0027] Preferably, the forsterite powder has a SiO2 content of ≥40wt%, a MgO content of ≥50wt%, and a powder particle size of <600 mesh;
[0028] The crystal inducing material is waste inorganic thermal insulation material, preferably waste thermal insulation bricks or waste thermal insulation boards;
[0029] More preferably, the components of the insulation brick waste and insulation board waste include xonotlite, tobermorite and silicon dioxide; the insulation brick waste or insulation board waste is crushed into powder, and the powder particle size is less than 10 μm.
[0030] The strength stabilizing material B of the present invention and the strength stabilizing material A jointly reduce the calcium-silicon ratio of the cement system, and can also form Mg(OH)2 during the high-temperature hydration process of cement, so that the cement paste has a certain expansibility; in addition, the filling and heterogeneous nucleation effect of nano-clay can refine the pore structure, and the synergistic effect with the forsterite powder with excellent temperature resistance greatly reduces the permeability of the cement paste, enhances the density and interface bonding ability of the cement paste, and thus improves the anti-channeling ability and mechanical properties of the cement paste.
[0031] The crystal inducing material of the present invention can be used as a seed material in the cement hydration process to induce the cement hydration product to quickly crystallize at high temperature to form more xonotlite and tobermorite, thereby improving the high temperature resistance of cement paste and avoiding the decline of cement paste strength.
[0032] Furthermore, the toughness modifier is prepared by uniformly mixing sillimanite powder, expanded graphite and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.
[0033] Furthermore, the purity of the sillimanite powder is greater than 99wt%, and the powder particle size is 325 meshes.
[0034] Furthermore, the expanded graphite has a particle size of 80 meshes.
[0035] Furthermore, the purity of the phenyl silicone rubber powder is greater than 99wt%, and the powder particle size is 325 meshes.
[0036] On the other hand, a method for preparing a heat-resistant composite modified material for cementing cement is provided, wherein a strength modifier type I, a strength modifier type II, and a toughness modifier are uniformly mixed in proportion to obtain the heat-resistant composite modified material for cementing cement.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1. The heat-resistant composite modified material for cementing provided by the present invention can effectively improve the high-temperature compressive strength and toughness of cement stone, and can ensure that the compressive strength of cement stone does not decline under high-temperature environment. The present invention uses a large amount of solid waste as the main raw material, and has the characteristics of green environmental protection, low cost and excellent performance.
[0039] 2. The waste glass powder, fused quartz sand and tungsten tailings powder used in the strength modifier type I of the present invention are mainly crystalline or amorphous silicon dioxide. The main components of the strength modifier type II also include active silicon dioxide and alumina. Under the joint action of the two, on the one hand, the calcium-silicon ratio of the cement system is reduced; on the other hand, the hydration rate is controlled by different crystal forms of silicon dioxide, thereby regulating the formation of high-temperature hydration products. Active aluminum ions can also be introduced under the dissociation effect of the strength modifier type II to promote the formation of temperature-resistant aluminosilicate minerals, thereby further improving the strength and temperature resistance of the system.
[0040] 3. The strength modifier type II of the present invention loads the crystal inducing material inside the pores and on the surface of the strength stabilizing material A, which not only greatly accelerates the formation of xonotlite and tobermorite, but also induces the formation of aluminosilicate minerals and aluminum substitutes, further enhancing the high temperature resistance of cement paste. In addition, it can also make the cement paste have a certain degree of expansion and enhance the interface bonding ability. On the one hand, the small amount of carbon powder in the strength stabilizing material A can refine the pore structure under the synergistic effect of the strength stabilizing material B, reduce the permeability of the cement paste, and increase the density of the cement paste; on the other hand, it can also synergize with the toughness modifier to provide crystallization points for the hydration products to promote hydration.
[0041] 4. The toughness modifier of the present invention has excellent high temperature resistance. It combines inorganic fibrous materials (sillimanite powder), rubber elastic particles (phenyl silicone rubber powder) and flexible particles (expanded graphite) and increases not only the specific surface area and roughness of the toughness modifier through surface modification, but also the polar groups on the surface of the toughness modifier. This enhances the compatibility of the toughness modifier with cement stone, and the cement hydration products can adhere to the surface of the toughness modifier, so that the interfacial bonding strength in the interface transition zone is enhanced, thereby improving the mechanical properties of the cement stone. Under the synergy and action modification of each component, not only the elastic toughness and impact resistance of the cement stone are enhanced, but also the compressive strength of the cement stone is improved. In addition, the strength modifier type II mesocrystalline inducing material has certain inorganic fibers, which can work together with the toughness modifier to further improve the elastic toughness and impact resistance of the cement stone. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0043] The cement slurries in the following examples were prepared according to GB / T19139 standard, wherein the G-grade oil well cement was provided by Jiahua Special Cement Co., Ltd.
[0044] Example 1
[0045] As a preferred embodiment of the present invention, a heat-resistant composite modified material for cementing cement in this embodiment has a specific composition as shown in Table 1 below:
[0046] Table 1
[0047] raw material Weight ratio (%) Strength Modifier Type I 30 Strength Modifier Type IⅡ 60 Toughness modifier 10
[0048] The strength modifier type I of this embodiment is a mixture of waste glass powder, tungsten tailings powder, and fused quartz sand in a mass ratio of 1:1:1.
[0049] The strength modifier type II of this embodiment is a mixture of strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2.
[0050] The toughness modifier of this embodiment is prepared by uniformly mixing sillimanite powder, expanded graphite, and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.
[0051] Weigh and mix the raw materials according to the proportions in Table 1 to obtain a heat-resistant composite modified material 1# for cementing cement.
[0052] Example 2
[0053] As a preferred embodiment of the present invention, a heat-resistant composite modified material for cementing cement in this embodiment has a specific composition as shown in Table 2 below:
[0054] Table 2
[0055] raw material Weight ratio (%) Strength Modifier Type I 35 Strength Modifier Type IⅡ 57 Toughness modifier 8
[0056] The strength modifier type I of this embodiment is a mixture of waste glass powder, tungsten tailings powder, and fused quartz sand in a mass ratio of 1:1:1.
[0057] The strength modifier type II of this embodiment is a mixture of strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2.
[0058] The toughness modifier of this embodiment is prepared by uniformly mixing sillimanite powder, expanded graphite, and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.
[0059] Weigh and mix the raw materials according to the proportions in Table 2 above to obtain heat-resistant composite modified material 2# for cementing cement.
[0060] Example 3
[0061] As a preferred embodiment of the present invention, a heat-resistant composite modified material for cementing cement in this embodiment has a specific composition as shown in Table 3 below:
[0062] Table 3
[0063] raw material Weight ratio (%) Strength Modifier Type I 40 Strength Modifier Type IⅡ 55 Toughness modifier 5
[0064] The strength modifier type I of this embodiment is a mixture of waste glass powder, tungsten tailings powder, and fused quartz sand in a mass ratio of 1:1:1.
[0065] The strength modifier type II of this embodiment is a mixture of strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2.
[0066] The toughness modifier of this embodiment is prepared by uniformly mixing sillimanite powder, expanded graphite, and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.
[0067] Weigh and mix the raw materials according to the proportions in Table 3 above to obtain heat-resistant composite modified material 3# for cementing cement.
[0068] Example 4
[0069] As a preferred embodiment of the present invention, a heat-resistant composite modified material for cementing cement in this embodiment has a specific composition as shown in Table 4 below:
[0070] Table 4
[0071] raw material Weight ratio (%) Strength Modifier Type I 40 Strength Modifier Type II 55 Toughness modifier 5
[0072] The strength modifier type I of this embodiment is a mixture of waste glass powder, tungsten tailings powder and fused quartz sand in a mass ratio of 1:2:1.
[0073] The strength modifier type II of this embodiment is a mixture of strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2.
[0074] The toughness modifier of this embodiment is prepared by uniformly mixing sillimanite powder, expanded graphite, and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.
[0075] Weigh and mix the raw materials according to the proportions in Table 4 above to obtain heat-resistant composite modified material 4# for cementing cement.
[0076] Example 5
[0077] As a preferred embodiment of the present invention, a heat-resistant composite modified material for cementing cement in this embodiment has a specific composition as shown in Table 5 below:
[0078] Table 5
[0079] raw material Weight ratio (%) Strength Modifier Type I 40 Strength Modifier Type II 55 Toughness modifier 5
[0080] The strength modifier type I of this embodiment is a mixture of waste glass powder, tungsten tailings powder and fused quartz sand in a mass ratio of 2:2:1.
[0081] The strength modifier type II of this embodiment is a mixture of strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2.
[0082] The toughness modifier of this embodiment is prepared by uniformly mixing sillimanite powder, expanded graphite, and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.
[0083] Weigh and mix the raw materials according to the proportions in Table 5 above to obtain heat-resistant composite modified material 5# for cementing cement.
[0084] Comparative Example 1
[0085] This comparative example is a control group, which is a conventional high-temperature cementing cement, and its specific components include 65wt% of G-grade oil well cement and 35wt% of quartz sand in weight percentage.
[0086] Comparative Example 2
[0087] This comparative example is the same as Example 1, except that the strength modifier type I does not contain fused quartz sand, and a cementing cement material*1 is obtained.
[0088] Comparative Example 3
[0089] This comparative example is the same as Example 1, except that the strength modifier type II does not contain a crystal inducing material, and a cementing cement material*2 is obtained.
[0090] Comparative Example 4
[0091] This comparative example is the same as Example 1, except that the toughness modifier does not contain phenyl silicone rubber powder, and a material for cementing cement*3 is obtained.
[0092] Test Case
[0093] According to GB / T 19139 standard, cement slurry was prepared with a water-cement ratio of 0.44. The materials of Examples 1 to 5 and Comparative Examples 2 to 4 of the present invention were made into cement slurries according to a dosage of 35wt% and a dosage of 65wt% of G-grade oil well cement, and the conventional high-temperature cementing cement of Comparative Example 1 was used as the comparative cement slurry. After each cement slurry was poured into a copper mold for molding, it was placed in a high-temperature curing kettle for curing. The curing temperature was 260°C, and the curing period was 2d, 7d, and 28d. The compressive strength change was detected, and the permeability of the cement stone was tested. The test results are shown in Table 6. The cement stone after curing and molding was cored, and then a triaxial mechanical property test was performed. The cement stone mechanical test standard is based on GB / T50266-2013 "Engineering Rock Test Method Standard", and the equipment used in the experiment is RTR-1000 triaxial rock mechanics test, and the test results are shown in Table 7.
[0094] Table 6
[0095]
[0096]
[0097] From the data in Table 6 above, it can be seen that compared with Comparative Example 1, the cement paste formed by Examples 1 to 5 has a compressive strength greater than 36 MPa after a certain curing period, and the strength does not decline in the later period, and the permeability is less than 0.3 mD. This shows that the present invention can effectively improve the density and high-temperature compressive strength of cement paste, and can effectively inhibit the decline of cement paste strength. In addition, the compressive strength and permeability of Example 1 are better than those of Comparative Examples 2 to 4, indicating that there is a synergistic effect between the components in the present invention.
[0098] Table 7
[0099]
[0100] According to the data in Table 7 above, compared with Comparative Example 1, the present invention can effectively reduce the elastic modulus of cement stone in a high temperature environment, improve the high temperature toughness of cement stone, and ensure the engineering requirements of cementing cement stone in a high temperature environment. In addition, compared with the results of Comparative Examples 2 to 4, the components in the present invention have a synergistic effect, and the lack of any one of them cannot achieve the expected effect of the present invention.
[0101] In summary, the present invention can improve the density and strength of cement paste, effectively inhibit the decline of cement paste strength, reduce the elastic modulus of cement paste in a high temperature environment, improve the high temperature toughness of cement paste, and the components have a synergistic effect. The lack of any one of them cannot achieve the expected effect of the present invention.
[0102] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.
Claims
1. A heat-resistant composite modified material for cementing cement, characterized in that: The following raw materials are included in weight percentage: Strength modifier type I: 30-40wt%; Strength modifier type II: 55-60wt%; Toughness modifier: 5-10wt%.
2. The heat-resistant composite modified material for cementing cement according to claim 1, characterized in that: The strength modifier type I is prepared by mixing waste glass powder, tungsten tailings powder and fused quartz sand in a mass ratio of (1-2):(1-2):
1.
3. The heat-resistant composite modified material for cementing cement according to claim 2, characterized in that: The SiO2 content of the waste glass powder is ≥75wt%, and the powder particle size is 800 mesh; the SiO2 content of the tungsten tailings powder is ≥70wt%, the Al2O3 content is ≥10wt%, and the powder particle size is 325 mesh; the SiO2 content of the fused quartz sand is ≥99wt%, and the powder particle size is 325 mesh.
4. The heat-resistant composite modified material for cementing cement according to claim 1, characterized in that: The strength modifier type II is a mixture of strength stabilizing material A, strength stabilizing material B and crystal form inducing material in a mass ratio of 7:1:2, and the preparation method is as follows: S11, mixing the strength stabilizing material A and the crystal inducing material and placing them in a sealed stirring tank, using anhydrous ethanol as a solvent with a liquid-to-solid ratio of 5:1, stirring at room temperature for 48 hours to form slurry A; S12, separating the slurry A from the solid and liquid, and drying the slurry to obtain powder A; S13, mix the powder A and the strength stabilizing material B evenly to obtain a strength modifier type II.
5. The heat-resistant composite modified material for cementing cement according to claim 4, characterized in that: The strength stabilizing material A is made by mixing waste siliceous shale, biomass slag and coal gasification slag in a mass ratio of 2:1:1; Preferably, the SiO2 content of the waste siliceous shale is ≥85wt%, and the waste siliceous shale is crushed and ground to form a powder with a particle size of 600 mesh; Preferably, the SiO2 content of the biomass slag is ≥65wt%, the Al2O3 content is ≥15wt%, and the biomass slag is dried and ground to form a powder with a particle size of 600 mesh; Preferably, the coal gasification slag has a SiO2 content of ≥55wt%, an Al2O3 content of ≥20wt%, a carbon content of ≥10wt%, and a particle size of 375 mesh; The strength stabilizing material B is a mixture of nano clay, waste magnesia brick powder and forsterite powder in a mass ratio of 1:1:2; Preferably, the SiO2 content of the nanoclay is ≥47wt%, and the Al2O3 content is ≥40wt%; Preferably, the MgO content of the waste magnesia brick powder is ≥90wt%, and the powder particle size is 325 mesh; Preferably, the forsterite powder has a SiO2 content of ≥40wt%, a MgO content of ≥50wt%, and a powder particle size of <600 mesh; The crystal inducing material is waste inorganic thermal insulation material, preferably waste thermal insulation bricks or waste thermal insulation boards; More preferably, the components of the insulation brick waste and insulation board waste include xonotlite, tobermorite and silicon dioxide; the insulation brick waste or insulation board waste is crushed into powder, and the powder particle size is less than 10 μm.
6. The heat-resistant composite modified material for cementing cement according to claim 1, characterized in that: The toughness modifier is prepared by uniformly mixing sillimanite powder, expanded graphite and phenyl silicone rubber powder in a mass ratio of 10:1:1 and then subjecting the mixture to plasma modification.
7. The heat-resistant composite modified material for cementing cement according to claim 6, characterized in that: The purity of the sillimanite powder is greater than 99wt%, and the powder particle size is 325 meshes.
8. The heat-resistant composite modified material for cementing cement according to claim 6, characterized in that: The particle size of the expanded graphite is 80 meshes.
9. The heat-resistant composite modified material for cementing cement according to claim 6, characterized in that: The purity of the phenyl silicone rubber powder is greater than 99wt%, and the powder particle size is 325 meshes.
10. The method for preparing a heat-resistant composite modified material for cementing cement according to any one of claims 1 to 9, characterized in that: The strength modifier type I, the strength modifier type II and the toughness modifier are uniformly mixed in proportion to obtain the heat-resistant composite modified material for cementing cement.
Citation Information
Patent Citations
A high-temperature oil well cement stone elastic material and its preparation method
CN107973538B
A high-temperature resistant and tough material and its preparation method
CN109609107B
Ultra-high temperature elasticity and toughness agent for oil and gas well cementing and composition and application thereof
CN110257030A
Cementing composition, composite cementing material and cementing fluid
CN112299736A
Well cementation cement for high-temperature deep well, and preparation method and application thereof
CN110862245A